2021
DOI: 10.21873/anticanres.15138
|View full text |Cite
|
Sign up to set email alerts
|

Crypts in Asymmetric Fission in Endoscopic Biopsies from Swedish Patients With Inflammatory Bowel Disease

Abstract: Background/Aim: We previously found crypts in symmetric fission (CSF) and in asymmetric fission (CAF) in colectomy-specimens with ulcerative colitis. We now analyzed CSF and CAF (CSAF) in biopsies from 80 patients with inflammatory bowel disease (IBD) without dysplasia or carcinoma. Patients and Methods: One unselected doublebiopsy from affected endoscopic areas was investigated in the 80 cases. Results: A total of 353 crypts in fission were found. The median number of CAF/biopsy was 3.7 and for CSF/biopsy, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…CSFs are the results of a homeostatic compensatory mechanism of boosted crypt production in mucosal areas previously occupied by chronic inflammation (2,9). Although the possible significance of CAF could not be assessed from these studies, their occurrence in the colonic mucosa of IBD patients appears to suggest a genuine pathologic aberration in cryptogenesis.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…CSFs are the results of a homeostatic compensatory mechanism of boosted crypt production in mucosal areas previously occupied by chronic inflammation (2,9). Although the possible significance of CAF could not be assessed from these studies, their occurrence in the colonic mucosa of IBD patients appears to suggest a genuine pathologic aberration in cryptogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…In the Swedish study (9), one unselected endoscopic biopsy from endoscopic affected areas in the colon was also investigated in the 80 IBD patients (40 with UC and 40 with CCs). Table II Thus, despite that German and Swedish populations dwell in disparate geographical areas, and are being subjected to different ecological factors, the proportions of CSF and CAF are similar, strongly suggesting that CF and in particular CAF, develop in IBD independently of the local environmental conditions in the two regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, none of the aforementioned grading systems includes the histologic characteristics of branching crypts in UC. In previous publications, we described in detail, the histologic characteristics of crypt branching in UC (13)(14)(15)(16). These studies, based on single colonic biopsies in patients with UC showed two histologic phenotypes of branching crypts: i) crypts in symmetric branching (CSB) and ii) crypts in asymmetric branching (CAB).…”
mentioning
confidence: 99%